Gut Microbiota Dysbiosis as Risk and Premorbid Factors of IBD and IBS Along the Childhood–Adulthood Transition. Issue 2 (February 2016) - Putignani, Lorenza; Del Chierico, Federica; Vernocchi, Pamela; Cicala, Michele; Cucchiara, Salvatore; Dallapiccola, Bruno
Abstract : Abstract: Gastrointestinal disorders, although clinically heterogeneous, share pathogenic mechanisms, including genetic susceptibility, impaired gut barrier function, altered microbiota, and environmental triggers (infections, social and behavioral factors, epigenetic control, and diet). Gut microbiota has been studied for inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS) in either children or adults, while modifiable gut microbiota features, acting as risk and premorbid factors along the childhood-adulthood transition, have not been thoroughly investigated so far. Indeed, the relationship between variations of the entire host/microbiota/environmental scenario and clinical phenotypes is still not fully understood. In this respect, tracking gut dysbiosis grading may help deciphering host phenotype–genotype associations and microbiota shifts in an integrated top–down omics-based approach within large-scale pediatric and adult case-control cohorts. Large-scale gut microbiota signatures and host inflammation patterns may be integrated with dietary habits, under genetic and epigenetic constraints, providing gut dysbiosis profiles acting as risk predictors of IBD or IBS in preclinical cases. Tracking dysbiosis supports new personalized/stratified IBD and IBS prevention programmes, generating Decision Support System tools. They include (1) high risk or flare-up recurrence -omics-based dysbiosis profiles; (2) microbial and molecular biomarkers of health and disease; (3) -omics-based pipelines for laboratory medicine diagnostics; (4) health apps for self-management of score-based dietary profiles, which can be shared with clinicians for nutritional habit and lifestyle amendment; (5) -omics profiling data warehousing and public repositories for IBD and IBS profile consultation. Dysbiosis-related indexes can represent novel laboratory and clinical medicine tools preventing or postponing the disease, finally interfering with its natural history. Abstract : Article first Published online 21 October 2015